Hydrocolloid-assisted strategies for developing low-glycemic index rice: Mechanistic roles of starch modification, bioactive fortification, and processing innovations - Ketnawa S; Tian J; Ogawa Y; Singh J; Kaur L; Phongthai S; Tanongkankit Y; Issara U; Phungamngoen C; Donlao N (Elsevier B V, 2026)
Rice, a staple for over half the global population, is associated with a high glycemic index (GI), contributing to diabetes, obesity, and related metabolic disorders. This review explores hydrocolloid-assisted strategies for developing low-GI rice, focusing on their mechanistic role in reducing starch digestibility. Hydrocolloids such as pectin, guar gum, xanthan gum, and β-glucan influence starch retrogradation, enzyme accessibility, and amylose-lipid complex formation, which slow glucose release. Processing techniques like retrogradation, germination, fermentation, and extrusion modify starch–protein–lipid interactions, enhancing GI reduction. Additionally, fortification with rice-derived bioactives, including polyphenols, flavonoids, γ-aminobutyric acid, dietary fibers, and local herbs (e.g., turmeric, garlic, green tea, mulberry leaves, pandan leaves, and butterfly pea flowers) reduces digestibility and promotes antioxidant and gut health benefits. These strategies are integrated into the mechanistic integration, highlighting how molecular, structural, and processing modifications collectively reduce GI. The review also addresses limitations and challenges, including variability in GI testing methods, sensory acceptability issues, nutrient loss during processing, and scalability for industry adoption. A summary table of human clinical trials evaluating the glycemic response to low-GI rice is provided to enhance practical relevance. Future research directions include multi-omics approaches for rice starch modification, intelligent processing technologies, and targeted nutrition interventions for at-risk populations, such as diabetics and the elderly, to optimize structure–function relationships and facilitate the adoption of low-GI rice in mainstream food systems.
Keywords: Low-glycemic index; Bioactive fortification; Starch modification; Hydrocolloid strategies; Processing innovations